Effects of ractopamine hcl (paylean) and α-lipoic acid on the growth performance and carcass characteristics of finishing pigs - J R Bergstrom; Terry A Houser; Michael D Tokach; J A Gunderson; A N Gipe; J Jacela; J M Benz; R C Sulabo; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
A total of 48 gilts (initially 211 lb) were used to evaluate the effects of ractopamine HCl and Î±-lipoic acid on finishing pig performance and carcass characteristics. Pigs were blocked by weight and randomly allotted to 1 of 4 dietary treatments in a 22-d experi-ment. Pigs were fed corn-soybean meal-based diets. Treatments were arranged as a 2 × 2 factorial with main effects of ractopamine HCl (0 or 9 g/ton) and Î±-lipoic acid (0 or 300 ppm). For overall growth performance (d 0 to 22), ADG tended (P<0.09) to be greater for pigs fed ractopamine HCl. Although F/G improved (P<0.01) for pigs fed ractopamine HCl, there was a trend (P<0.07) for an interaction between ractopamine HCl and Î±-lipoic acid. For pigs fed diets without ractopamine HCl, added Î±-lipoic acid numerically improved F/G, whereas in pigs fed ractopamine HCl, added Î±-lipoic acid numerically worsened F/G. Average final weight tended (P<0.06) to be greater for pigs fed ractopamine HCl. No other differences in growth performance were observed. For the comparison of carcass characteristics, average live weight, HCW, yield, loin eye area at the 10th rib, and standardized fat-free lean were increased (P<0.04) for pigs fed ractopamine HCl. Average backfat thickness tended (P<0.06) to decrease for pigs fed ractopamine HCl. Tenth-rib backfat increased (P<0.05) for pigs fed Î±-lipoic acid, and the percent fat-free lean of pigs fed Î±-lipoic acid tended (P<0.10) to decrease as a result. In conclusion, the growth performance and carcass characteristics of pigs fed ractopamine HCl were improved. Feeding 300 ppm of Î±-lipoic acid did not affect growth performance but did tend to increase carcass fat content.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Carcass characteristics; Finishing pigs; Ractopamine HCl